Constantly changing, constantly adapting: Lives and life-course data of children and childhood social care - Allik, Mirjam; Bailey, Grace; Cummings, Aimee; Falster, Kathleen; Gilbert, Ruth; Griffiths, Lucy; Jay, Matt; Nickel, Nathan; Phillips-Beck, Wanda; Pilkington, Rhiannon (International Journal of Population Data Science, 2024)
Objectives Childhood social care can lead to lifelong problems affecting health, educational attainment and other areas of a person’s life. Improving outcomes for children are therefore key policy objectives in many nations. The aim of this workshop was to inspire and drive forward life-course research on childhood social care internationally. Approach The workshop included presentations on the themes of the data jigsaw across the family life-course and data sovereignty and engagement. Presentations under each theme were followed by group activities and discussions. Results Administrative data collections that include longitudinal details on childhood social care, developmental, health and other outcomes are becoming increasingly available for researcher purposes. Examples include the BEBOLD platform and the New South Wales Child E-Cohort in Australia, ECHILD in England and the Welsh SAIL Databank. First nations data sovereignty and engagement of childhood social care recipients has become a norm in many nations and led to improvements in research, including in methodology and interpretation of results. Together, improved access to data and meaningful stakeholder engagement can inform policy and practice to improve outcomes for children and young people. Conclusions Barriers exist to understanding the family and home environments, such as very limited or no information about the fathers and other household members. Capturing populations who move between jurisdictions, e.g. migrants, is limited as administrative data is difficult to share across devolved nations/federated states. In some cases, a mismatch exists between expectations of meaningful engagement and institutional/research culture, resource and skill availability.